Tuned inerter dampers with linear hysteretic damping. (1st July 2020) - Deastra, Predaricka; Wagg, David; Sims, Neil; Akbar, Mahesa
Summary: This paper explores the influence of linear hysteretic damping on the performance of passive tuned‐inerter devices. An inerter is a device that produces a force proportional to the relative acceleration across its two terminals; devices incorporating inerters have received widespread attention in the earthquake engineering community, because they offer the ability to improve the seismic response of structures. However, the majority of this research has assumed that the damping components within the tuned‐inerter device exhibit viscous, rather than hysteretic, damping. This restriction imposes an essential question on how the hysteretic damping model will change the performance of the device compared with the viscous damping model. It is shown that the response of viscous and hysteretic inerter systems have significant differences in displacement amplitude due to the frequency dependency of the damping. Therefore, a new formulation for obtaining the optimum loss factor of the hysteretic damping in the inerter system is proposed. Next, the challenges associated with accurately predicting the time‐response of a hysteretically damped system are discussed. A numerical time‐integration method is extended to address these challenges, using a new formulation that has the benefit of being broadly applicable to multidegree‐of‐freedom hysteretic linear systems and nonstationary random signals. The results show that the earthquake responses from the hysteretic damping model can differ significantly from the ones obtained via the viscous model.